A review of high-resolution X-ray computed tomography applied to petroleum geology and a case study. (September 2019) - Zhang, Penghui; Lee, Yong Il; Zhang, Jinliang
Highlights: The development of micro-CT as a complementary tool to laboratory core tests has been widely applied to the study of petroleum geology. Micro-CT is performed on tight-gas sandstones to quantify the internal architecture in 3D and to carry out fluid-flow modelling. An integration of 3D pore characterization and fluid-flow visualization results in good agreement with reservoir quality predicted by textural, depositional and diagenetic variations. Abstract: High-resolution X-ray computed tomography (micro-CT) has been widely used as a non-destructive technique, allowing 3D imaging and analysis of internal features of various objects. This paper briefly describes this technique used in the field of petroleum geology, with an example of its applications for tight-gas sandstone reservoirs. Reservoir quality controls the storage, distribution, and flow of fluids within tight-gas sandstone reservoirs, however, it remains difficult to predict. Although our earlier work has reported that reservoir quality of non-marine tight-gas sandstones in the Lower Cretaceous Denglouku Formation in the Songliao Basin, China is controlled by sedimentary texture, depositional facies, and diagenesis, there is lack of information on the effectiveness of pore-lining clay minerals on pore preservation and pore connectivity. Micro-CT is performed on two representative sandstone samples from the studied Denglouku sandstones, (1) to quantify the internal architecture in 3D and (2) to carry out fluid-flow modelling to determine the effective transport capacity. The quantitative 3D imaging and modelling by means of micro-CT provides a better insight of pore network connectivity and pore preservation characteristics at the pore scale. Here, we develop a procedure that integrates pore-scale imaging and modelling with depositional and diagenetic processes in the context of non-marine tight-gas sandstones. Micro-CT data are compared with results derived from core and wireline log interpretation as well as laboratory measurements on the same core samples, which results in good agreement and supports the prediction of pore preservation effectiveness of the sandstones containing pore-lining chlorite and illite with relatively high grain-surface coverage. It opens a potential opportunity for a pore-to-core upscaling approach to predict reservoir quality for tight-gas sandstones.